ZAKAT-ORCHESTRATED EMPOWERMENT PLATFORM: A CONCEPTUAL MODEL FOR INCLUSIVE FINANCIAL ACCOUNTABILITY AMONG WOMEN MICRO-ENTREPRENEURS - Budi Dharma; Santi Novani; Oktofa Yudha Sudrajad; Kyoichi Kijima (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2026)
This study examines why prevailing financing arrangements often fail to empower women micro-entrepreneurs, and develops a Zakat-based service architecture to address gaps in inclusion, capability conversion, and post-disbursement support. Guided by an abductive, design-science–oriented, and pragmatic stance, this study uses a multimethodology approach combining (i) diagnostic regressions based on a purposive survey of 302 unbanked women micro-entrepreneurs in Medan, (ii) interpretive triangulation through 10 semi-structured interviews, four reflective discussions, and institutional documents, and (iii) iterative artifact construction with plausibility checks through expert reviews in service systems and Islamic economics. The diagnostic results show that loan size is governed by rule-based eligibility criteria, namely repayment capacity, own capital, and collateral, while larger loans and higher operational spending do not systematically translate into sales growth. Complementary evidence also reveals substantial gaps in debt-management literacy. Drawing on Service-Dominant Logic, Service Systems Theory, behavioral finance, and Maqasid al-Shariah, this study develops the Zakat Service Platform for Women’s Empowerment, comprising five constructs: Access Equity, Effective Capital Use, Financial Capability, Relational Support, and Motivational Alignment. These are operationalized in the Zakat-Orchestrated Empowerment Platform (ZOEP) through Kijima’s 4C and a two-layer service system design that repositions amil as the platform orchestrators. This study proposes that Zakat institutions pilot ZOEP modules, including tiered verification, milestone-based disbursement, embedded capability tools, and mentoring loops, and evaluate the outcomes longitudinally while safeguarding justice, benefit, and dignity.